Profile of Students' Mathematical Problem-Solving Ability in View of Adversity Quotient - Suci Charolina; Suhendra (RANGE: Jurnal Pendidikan Matematika, 2025)
The Adversity Quotient (AQ) refers to individuals' ability to recognize challenges, apply their intelligence to these challenges, and turn them into problems to be solved. The low ability of students to solve mathematical problems is a major issue that needs to be analyzed more deeply from an AQ perspective. This study aims to analyze and describe students' mathematical problem-solving ability based on AQ, with the categories of climber, camper, and quitter. This qualitative research uses a case study method conducted on IX students at an SMP in Bandung, West Java. The subjects were three people who represented each AQ category. Data were collected through questionnaires, tests, and interviews. After that, the collected data were analyzed using the Miles and Huberman model, which involves the stage of data reduction, data presentation, and conclusion drawing/verification. The results of this study show that there are differences in mathematical problem-solving ability based on three categories of adversity quotient. Students in the climber category showed excellent ability to solve problems by fulfilling four problem-solving indicators: identifying problems, developing strategies, implementing strategies, and re-examining the results of the solution. Meanwhile, camper category students showed sufficient problem-solving ability by fulfilling three indicators: identifying problems, developing strategies, and implementing strategies. On the other hand, students in the quitter category showed low problem-solving ability and could only fulfill one indicator, namely identifying problems.